EVALUASI KINERJA ORGANISASI DENGAN PENDEKATAN BALANCED SCORECARD DI KPP PRATAMA DEPOK CIMANGGIS - Anggit Saghfira SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This research was conducted in a public sector organization, KPP Pratama Depok Cimanggis to measure its performance using Balanced Scorecard, which consists of financial, customer, internal business process, and learning and growth perspectives. They are interrelated in establishing an organizational performance profile, whose final result is shown in a scorecard. This qualitative research uses a case study. The result of this study indicates that the performance of KPP Pratama Depok Cimanggis, based on the perspectives is good with the average value of 3.71. The total score of 74 is not as expected. Learning and growth has the highest score, which is 4.33 (very good), and customer has the lowest score, which is 2.8 (poor). Internal business process has the score of 4.04 (very good), and financial has the score of 3.65 (good) criteria. Strategic steps are needed for future planning to improve the quality of service by prioritizing friendliness, efficiency and effectiveness so that the tax office can get more taxpayers without losing the current taxpayers. Furthermore, counselling and education through either social media or direct approach can also be an effective way to expand their promotion area and visiting agenda which in turn can improve their strategies in sales and marketing and increase public awareness about the importance being registered as taxpayers. In addition, they should simplify their online and offline business process and enhance employee training and development to create quality human resources and firm control over employees. Keywords: Balanced Scorecard, implementation, performance, KPP Pratama Depok Cimanggis